Oxaliplatin-induced rhabdomyolysis in a postoperative rectal cancer patient: a case report and literature review - Lin Yang; Hongna Han; Zihua Guo; Ming Tian; Weiping Chang; Zhengrong Chen; Chao Sun (Frontiers in Pharmacology, 2026)
This report describes the diagnosis and treatment of rhabdomyolysis associated with intravenous oxaliplatin administration in a patient undergoing postoperative chemotherapy for rectal cancer. The patient was a 73-year-old man who underwent laparoscopic robot-assisted radical resection for rectal cancer, pathologically staged as pT4aN1cM0 (IIIB). Postoperative chemotherapy was administered using the XELOX regimen. During the fourth cycle of chemotherapy, 2 h after completion of oxaliplatin infusion, the patient developed involuntary muscle twitching in both lower limbs accompanied by lower limb weakness. The family reported that the patient had previously experienced these symptoms following oxaliplatin infusion. This episode was accompanied by decreased urine output and dark, tea-colored urine. Laboratory tests revealed elevated creatine kinase (CK) levels of 2064.8 U/L. Following a multidisciplinary consultation, the patient was diagnosed with rhabdomyolysis and received symptomatic treatment, including hydration, alkalinization, and platelet-boosting therapy. After 5 days of treatment, creatine kinase (CK) levels returned to normal, and the patient was discharged. Following discharge, the patient discontinued chemotherapy. At the 8-month follow-up, all laboratory parameters remained within normal ranges.